2021
DOI: 10.2196/24475
|View full text |Cite|
|
Sign up to set email alerts
|

Benchmarking Triage Capability of Symptom Checkers Against That of Medical Laypersons: Survey Study

Abstract: Background Symptom checkers (SCs) are tools developed to provide clinical decision support to laypersons. Apart from suggesting probable diagnoses, they commonly advise when users should seek care (triage advice). SCs have become increasingly popular despite prior studies rating their performance as mediocre. To date, it is unclear whether SCs can triage better than those who might choose to use them. Objective This study aims to compare triage accuracy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 24 publications
3
55
1
Order By: Relevance
“…Similar to a previous observational study analyzing the potential impact of Ada ( 12 ), the majority of patients (already being at the healthcare facility) declared that they would not have done anything differently after having used the DDSS. In line with previous work that showed a general risk adversity of symptom checkers ( 4 , 11 ), our results shows that DDSS suggestions would actually encourage patients to seek earlier care rather than turn to self-care or see a physician later. On the other hand, Meyer et al ( 13 ) reported that 14/26 (54%) of symptom checkers users given advice to proceed to the ED actually did.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to a previous observational study analyzing the potential impact of Ada ( 12 ), the majority of patients (already being at the healthcare facility) declared that they would not have done anything differently after having used the DDSS. In line with previous work that showed a general risk adversity of symptom checkers ( 4 , 11 ), our results shows that DDSS suggestions would actually encourage patients to seek earlier care rather than turn to self-care or see a physician later. On the other hand, Meyer et al ( 13 ) reported that 14/26 (54%) of symptom checkers users given advice to proceed to the ED actually did.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, DDSS evaluation studies largely focus on the evaluation of the diagnostic accuracy ( 4 , 10 , 11 ) and only few studies analyzed the usability and acceptability by their end-users, i.e., actual patients. A recent study conducted by the symptom checker company Ada Health suggests that the majority of patients (511/522, 97.8%) rated the symptom checker Ada as very easy or quite easy to use and would recommend it to a friend or relative (444/520, 85.3%) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some work has also explored the triage capabilities of checkers [5, 51, 60]. Studying the utility and triage capabilities of checkers are beyond the scope of this paper and have been set as future work in Section 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, almost two-thirds of adults search the Web for health information and roughly one-third utilize it for self-diagnosis , trying to discover by themselves the underlying causes of their health symptoms [36]. A recent study showed that half of the patients investigated their symptoms on search engines before visiting emergency departments [38, 51].…”
Section: Introductionmentioning
confidence: 99%
“…In the originally published manuscript, Reference 24 in the reference list was cited incorrectly. This citation has now been corrected to the reference listed below [1].…”
mentioning
confidence: 99%